Method of drainage of retroperitoneal fat at infected pancreatonecrosis - N. N. Merzlikin; A. V. Kuznetsov; V. I. Barabash; R. V. Sorokin (Бюллетень сибирской медицины)
The aim of this study was to improve the results of treatment of patients with infected pancreatonecrosis complicated with phlegmon of retroperitoneal fat. Toward this end, the following tasks were formulated: to develop a new way of drainage of the retroperitoneal fat at infected pancreatonecrosis — retroperitoneostomy and to analyze comparatively the efficiency of traditional methods of drainage of the pancreatic gland zone at infected pancreatonecrosis (omnetobursotomy, lumbostomy) with retroperitoneostomy.The analysis was based on the results of examination and treatment of 60 patients with pancreatonecrosis complicated with phlegmon of retroperitoneal fat, who were operated in surgical departments of the Tomsk municipal hospital no. 3 in 2004—2008.The use of retroperitoneostomy in the treatment of infected pancreatonecrosis complicated with phlegmon of retroperitoneal fat decreased postsurgical complications from 36.6 to 15.79% and lethality from 56.1 to 21,0%.